Undergraduate students’ modelling routes mediated by technology in the learning of linear transformations - Ramírez Montes, Guillermo Enrique (2021)
Technology-mediated mathematical modelling has been recognized as a significant learning context. This paper reports on a study aiming to characterize the modelling routes performed by Costa Rican undergraduate students when solving a mathematical modelling task using technological resources as a means to explore the concept of linear transformation. Data collected from audio records of students’ discussions, their written work, and GeoGebra files show that the group of two students we focus in this paper performed a linear modelling route, by creating a mathematical model with the software, which highlights the visual aspect and the geometric transformation concept.